2016
DOI: 10.1016/s0140-6736(15)01314-8
|View full text |Cite|
|
Sign up to set email alerts
|

Oral fingolimod in primary progressive multiple sclerosis (INFORMS): a phase 3, randomised, double-blind, placebo-controlled trial

Abstract: Novartis Pharma AG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
314
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 398 publications
(354 citation statements)
references
References 28 publications
9
314
2
10
Order By: Relevance
“…At baseline, the placebo population ( n  = 487) had a median age of 49 years, median of 5.7 years since onset of symptoms, median Expanded Disability Status Scale (EDSS)10 score of 4.5; and 13% of patients had gadolinium‐enhancing T1 (Gd+) lesions. Over the ≥3‐year course of the study, there was a mean of 0.5 new/enlarging T2 lesions per patient per year, and 8% of patients experienced a relapse 1. The study found no significant difference between fingolimod 0.5 mg and placebo for the composite primary endpoint, 3‐month confirmed disability progression according to worsening of any one of: EDSS, 25‐foot timed‐walk test (25'TWT),11 or nine‐hole peg test (9‐HPT) 11, 12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, the placebo population ( n  = 487) had a median age of 49 years, median of 5.7 years since onset of symptoms, median Expanded Disability Status Scale (EDSS)10 score of 4.5; and 13% of patients had gadolinium‐enhancing T1 (Gd+) lesions. Over the ≥3‐year course of the study, there was a mean of 0.5 new/enlarging T2 lesions per patient per year, and 8% of patients experienced a relapse 1. The study found no significant difference between fingolimod 0.5 mg and placebo for the composite primary endpoint, 3‐month confirmed disability progression according to worsening of any one of: EDSS, 25‐foot timed‐walk test (25'TWT),11 or nine‐hole peg test (9‐HPT) 11, 12.…”
Section: Methodsmentioning
confidence: 99%
“…Fingolimod reduced the risk of disability worsening in relapsing‐remitting MS (RRMS) and consistently reduced brain volume loss by more than 30% compared with placebo or interferon‐beta in three randomized, controlled clinical trials 7, 8, 9. In PPMS, however, fingolimod treatment did not reduce disability worsening or brain volume loss, perhaps suggesting differences in pathogenesis of both disability progression and brain volume loss between RRMS and PPMS 1. The question arises whether normalized brain volume and brain volume loss are associated with disability progression in PPMS.…”
Section: Introductionmentioning
confidence: 99%
“…Five years after disease onset she was enrolled in the phase III trial of fingolimod 0.5 mg/day in PPMS (INFORMS) 1. She had never been treated with a DMT before.…”
Section: Case Reportmentioning
confidence: 99%
“…It has also undergone a phase III trial in people with progressive MS (pwPMS) failing to show efficacy on the primary endpoint 1. A key mechanism of action of fingolimod is believed to be sequestering of pathogenic lymphocytes in lymph nodes2 thereby preventing entry into the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing progression is an essential treatment goal in PPMS, a goal that drugs tested in previous clinical studies failed to achieve 2, 3, 4. Ascertaining the absence of progression in both clinical trials and clinical practice requires reliable and comprehensive measures of disease progression.…”
mentioning
confidence: 99%